Materiality assessment in sustainability reporting : case study of the airline industry - Aryal, Nabin (2017)
Materiality has been heavily emphasized in different sustainability reporting guidelines to increase the quality of the sustainability reports and report issues that are most aligned with the company’s most significant economic, environmental and social issues. In this thesis materiality analysis in sustainability reporting is analyzed. Firstly, in the theoretical part, the concept of sustainability reporting and materiality is explained along with the provision of materiality in different reporting guidelines. In this research section, fifteen different airlines’ sustainability reports are analyzed to find out how the materiality analysis is carried out in the airlines. The study is focused on airlines because; air transportation is one of the most energy intensive forms of transportation that has major impacts on noise, local air pollution and GHG emission. The thesis concludes that materiality assessment is carried out improperly by most of the airlines and the process is not transparent as very less information is given regarding the assessment process. Similarly, there is need for more inclusive stakeholder involvement in the materiality assessment process. The research findings also showed differences in the number, theme and presentation of identified material issues by the airlines in their sustainability reports. The thesis contributes to the understanding of materiality in nonfinancial reporting and suggests appropriate method to carry out the materiality analysis in sustainability reporting. Further, research on this topic could be conducted by focusing the materiality analysis on single company or taking the stakeholders’ views on the identified material issues.